DUKUNGAN KELUARGA DALAM MEMENUHI KEBERSIHAN DIRI PADA PENDERITA STROKE (CVA) YANG MENGALAMI GANGGUAN MOTORIK - Orizani, Chindy Maria (Universitas Muhammadiyah Jember, 2016)
Most of stroke patients experienced motoric disorder, it led to the unfulfilled the basic need especially for personal hygiene deficit so family could gave support for fulfilled the patient need. Family support includes informational support, emotional support, esteem support, and instrumental support. Inadequate social support, proven to decrease mortility, easier to recover from illness among the stroke patients, better cognitive function, physical within normal limits, and a controlled emotional health. The purpose of this study was to proved the relationship between family support in meeting the needs of personal hygiene in stroke patients. There were 30 respondents who were selected using purposive sampling. Data was analyzed by computer software. The majority of respondents were 55-65 year old, male, married, was not working, long-suffering stroke 1-3 years. The result showed that there was a strong relationship between support families with personal hygiene needs in people with stroke (CVA) (p=0,000, r=0,693). The patients who got family support had better personal hygiene than not. So the family members should be involved in personal hygiene fulfillment.